We are much more than books - Harriss, E; Smith, C; Phillips, D; White, G; Steiner, K; Henry, M; Thurley, N; Roberts, N (Bodleian Libraries, University of Oxford, 2022)
We are much more than books. We are experts in systematic reviews, literature searches, training, research question formulation, databases, Boolean logic, and reference management. We are trainers, searchers, authors, and problem solvers. We help students and staff in the university and in the OUH NHS trust.